SURVEI POTENSI GAHARU DENGAN SISTEM AGROFORESTRI DI KECAMATAN XIII KOTO KAMPAR, KABUPATEN KAMPAR (STUDI KASUS: DESA PULAU GADANG DAN DESA KOTO MASJID) - Sulistiono, Nanang; Insusanty, Enny; azwin, azwin (Fakultas Kehutanan Universitas Lancang Kuning, 2018)
This study aims to determine the potential of gaharu with agroforestry system in the village of Pulau Gadang and Koto Masjid Village. The research was conducted in Desa Gadang Village and Koto Masjid Village. The data collected is then analyzed descriptively. Based on the results of reseach conducted by gaharu plant species is Aquilaria malaccensis with the potential of the plant in the village of Pulau Gadang which is 7 years old as 70 trees, 8 years 920 stems and 9 years as many as 440 stems. Meanwhile, Koto Masjid Village is at the age of planting 7 years as many as 100 stems, 8 years as many as 300 stems and 9 years as many as 400 stems. The potential of gaharu plants in the community of Pulau Gadang Village with an average land area of ​​1.09 Ha / farmer, the average number of gaharu-producing trees is 84.12 trees / farmers, and the average tree / Ha is 78.03 trees / Ha / farmers. While in Koto Masjid village with average land area is 1.2 Ha / farmer, average number of tree 145,45 trees / farmer, and average tree / Ha counted 68,67 tree / Ha / farmer.